Estudo das propriedades estruturais e magnéticas do sistema Cu1-xMxO (M = Fe, Ni, Al e Zn) - Pedra, Pablo Pedreira (2011)
In this work were obtained of Cu1-xMxO (M = Fe, Ni, Al e Zn, for 0 ≤ x ≤ 0,1 samples, using the co-precipitation method. These samples were studied using different techniques of characterization structural and magnetic. X-ray diffraction (XRD) results added to the Rietveld refinement analysis of the x-ray powder diffraction data shows that all samples present monoclinic the same structure of CuO with space group C2/c. The magnetization measurements as function of temperature (MvsT) show a fast suppress of TN for Fe-doped CuO samples, in contrast with (Ni, Zn and Al)-doped CuO. Synchrotron radiation XRD data at low temperature performed with show that the Cu0,9Fe0,1O and Cu0,9Ni0,1O samples present slow changes in the cell parameters, which it can be associated with the magnetic transition. Although the X-ray absorption (XAS) measurements performed in Cu K-edge show a variation in the density of unoccupied state in the p sublevel, appreciable changes in the local structure of these ions ban not be confirmed. On the other hand, measurements at the doping K and L2,3-edges confirm the existence of Ni2+ ions and oxygen vacancies and/or defect in your structure, already measurements performed in Cu0,9Fe0,1O sample shown the presence of Fe+2/Fe+3 mixed valence.